2022
DOI: 10.3389/fmicb.2022.1022783
|View full text |Cite
|
Sign up to set email alerts
|

Early life microbiota transplantation from highly feed-efficient broiler improved weight gain by reshaping the gut microbiota in laying chicken

Abstract: Starting phase of laying chicken life is the building stone for rearing and production stages. Since, fecal microbial transplantation (FMT) regulates the gut microbial diversity and affects the productive performance of the bird. The aim of this study is to evaluate the effect of FMT from feed-efficient broiler chicken could program the diversity of gut microbiota and growth of recipient native slow growing egg-laying chicks. For this, a total of 150 (one-day-old) Jing Hong chicks were randomly assigned into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…FMT has recently been investigated in animal agriculture as well, particularly in poultry. Recent studies have found that FMT improved weight gain and overall health of broiler chickens by reshaping the gut microbiota composition; specifically protected chicks from Salmonella enteritidis infection; and improved egg-laying performance in broiler breeders [ [146] , [147] , [148] ]. Besides FMT, probiotics can also be used to alter the microbiome and thus prevent or eradicate infection.…”
Section: Prevention and Control Of Zoonoses And Antimicrobial Resista...mentioning
confidence: 99%
“…FMT has recently been investigated in animal agriculture as well, particularly in poultry. Recent studies have found that FMT improved weight gain and overall health of broiler chickens by reshaping the gut microbiota composition; specifically protected chicks from Salmonella enteritidis infection; and improved egg-laying performance in broiler breeders [ [146] , [147] , [148] ]. Besides FMT, probiotics can also be used to alter the microbiome and thus prevent or eradicate infection.…”
Section: Prevention and Control Of Zoonoses And Antimicrobial Resista...mentioning
confidence: 99%
“…2a). Such a variety of functional attributes within major bacterial clades ags the risk of oversimplifying bacterial functional complexity when analysing gut microbiota features in terms of phylum-level ratios, as commonly done with the Firmicutes/Bacteroidota ratio 36,37 .…”
Section: Distillation Of Gene Annotations Reveals the Functional Comp...mentioning
confidence: 99%
“…Several studies have confirmed that. For example, Elokil et al (2022) demonstrated that transplanting gut microorganisms from high-feed efficiency broiler to laying hens specifically altered the community composition and functional characteristics of the cecum. Meanwhile, Wang et al (2022) pointed out that transfer the microbes of 208-day-old SPF adult chickens to newly hatched chickens reduced the negative impact and counteracted the lethal effect of Salmonella infection.…”
Section: Introductionmentioning
confidence: 99%